Ownership Structure and the Temptation to Loot : Evidence from Privatized Firms in the Czech Republic - Cull, Robert (World Bank, Washington, DC, 2014)
Using a new data set on privatized firms in the Czech Republic, the authors examine how the design of privatization affects outcomes. Earlier studies of privatization in the Czech Republic focused largely on how the broad distribution of shares through vouchers may have motivated the new owners to strip assets from the privatized firms. The authors find evidence for static asset stripping, but also for what Akerlof and Romer (1993) call looting - borrowing heavily with no intent to repay and using the loans for private purposes. This looting occurred because the larger privatized companies had privileged access to credit from state-controlled banks, which had little incentive to enforce debt contracts. The policy implications are significant: financial incentives and regulation are as important as ownership structure in the design of privatization.